Examining the Impact of Hybrid Work on Employee Performance and Engagement on Generation Z in Indonesia - Angreni, Dede Dwi; Mahyuni, Luh Putu (PT Mattawang Mediatama Solution, 2024)
This study aims to provide empirical evidence on the factors influencing the hybrid workplace model from the employer's perspective, as well as the intention of adopting hybrid work as the future of work to enhance performance. The theoretical framework combines the Theory of Performance and Development as a reference for the study. This is a quantitative research study that employs purposive sampling, selecting participants based on specific criteria. Data collection was conducted through a survey method using questionnaires distributed to 170 respondents. The analysis was performed using the SmartPLS 4.0 software.The empirical results show a strong correlation between work engagement and employee performance, with the integration of mediating factors. The findings indicate that better acceptance of the benefits of hybrid work and work-life balance by employees contributes to improved employee performance. Furthermore, evidence suggests that the path coefficient of hybrid work has the most dominant role in influencing employee performance and work engagement, particularly among Generation Z. This indicates that Generation Z possesses a forward-thinking approach to self-quality, enabling them to align their interests with their efforts to maintain their work quality.